2019
DOI: 10.1177/0093854819887991
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Structural Equation Model of Stress-Related Experiences Among Justice-Involved Youth: A Gender Comparison

Abstract: Youth involved in the juvenile justice system demonstrate greater risk of exposure to negative life experiences. The present study explores the prevalence of three stress-related experiences (sexual assault victimization, bullying/victimization, and minority sexual orientation) among newly arrested adolescents. Gender (biological sex) differences were examined as well as associations with sociodemographic characteristics, depressive symptoms, substance use, and sexually transmitted infection (STI). Factor anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Our findings are more in line with the stress research suggesting that females may be more sensitive to stress which may increase their risk of participating in youth delinquency (Gibson et al 2014). Although, typically, greater strain or stressors may manifest as mental health problems for females (Broidy and Agnew 1997; Dembo et al 2020; Hay 2003), it could be that in high-risk youth samples (like the FFCWS), exposure to a variety of ACEs may be more directly linked to externalizing problems, such as delinquency, for girls compared to boys. Further research is needed to continue to explore these gendered relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are more in line with the stress research suggesting that females may be more sensitive to stress which may increase their risk of participating in youth delinquency (Gibson et al 2014). Although, typically, greater strain or stressors may manifest as mental health problems for females (Broidy and Agnew 1997; Dembo et al 2020; Hay 2003), it could be that in high-risk youth samples (like the FFCWS), exposure to a variety of ACEs may be more directly linked to externalizing problems, such as delinquency, for girls compared to boys. Further research is needed to continue to explore these gendered relationships.…”
Section: Discussionmentioning
confidence: 99%
“…In the stress literature, females appear to have greater stress sensitivity compared to males. Specifically, females are more likely to report higher perceived stress scores compared to males (Myin-Germeys et al 2004; Rudolph and Hammen 1999) and greater stress sensitivity has been significantly associated with inwardly directed symptoms and distress for females (Gibson et al 2014), which often is associated with delinquent behaviors, such as substance use (Dembo et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Worse general health is also common among arrested populations. For example, arrested youth have been found to have higher rates of sexually transmitted infections (STIs) (Belenko et al, 2008), substance use, and parental incarceration and substance use in comparison to the general population (Dembo et al, 2020).…”
Section: The Justice System Continuum and Healthmentioning
confidence: 99%
“…Arrested youth often have higher unmet needs in comparison to youth in the general population (e.g., Dembo et al, 2018). Arrested youth exhibit elevated prevalence rates of depression and suicide ideation/attempts (Dembo et al, 2020; Kemp et al, 2021; Krupa et al, 2021). Across the juvenile justice system, studies reported past year suicide ideation ranging from 19%-50%; in comparison to high school youth who ranged from 12%–16% (Kemp et al, 2021; Wasserman & McReynolds, 2006) (for a review see Teplin et al, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%